Cluster TOF-SIMS imaging: A new light for in situ metabolomics? - Mas, Sebastian; Perez, Raul; Martinez Pinna, Roxana; Egido, Jesus; Vivanco, Fernando (My University, 2008)
The advent of metal cluster as a primary ion source in the late 1980s, made it feasible to probe surfaces for complex organic structures due to a reduced in-source fragmentation, and opened the door to the direct analysis of biological samples. Despite the mass range measurable by TOF secondary ion MS (SIMS) still being rather limited, the information obtained from cells and tis sues comes together with the technical innovations introduced in the last decade. In this article, we give a brief overview of the technique itself and make some emphasis on the advances in the last three years in the analysis of biological surfaces, particularly those with direct implication in the biomedical field; reviewing what kind of information this instrumentation will add to current tool in pathology.